Co-delivery of paclitaxel and temozolomide by CD133-B19 aptamer conjugated polyamidoamine dendrimer to U87 stem cells - Barzegarbehrooz, Amir (2020)
Glioblastoma multiforme (GBM) is 57% of all gliomas, and 48% of the primary central nervous system (CNS) tumors. Despite multimodal treatment, based on surgery, radiotherapy, and chemotherapy, and advancements in each approach, GBM remains characterized by a poor prognosis, with an estimated overall survival of less than 6% at 5 years post-diagnosis. The first-line systemic therapy is currently represented by temozolomide (TMZ), but the majority of patients relapse after 6 months. According to consensus, recurrence of the tumor and chemotherapy resistance acquisition are two distinguishing features of GBM that originating from glioblastoma stem cells (GSCs). To overcome the problems inherent in GBM chemotherapy, targeting GSCs through an intelligent drug delivery system has come to the forefront of GBM therapeutics. In this study, B19 aptamer, RNA aptamer with high sensitivity for recognizing the AC133 epitope and the CD133 protein, (Apt)-conjugated polyamidoamine (PAMAM) dendrimer nanoparticles (NPs), called Apt-NPs, were formulated for the co-delivery of paclitaxel (PTX) and TMZ to U87 stem cells. One of the most well-known TMZ-sensitive GBM cell lines is U87. The physicochemical properties of Apt-NPs such as size, zeta potential, and polydispersity index (PDI) were analyzed by dynamic light scattering (DLS). The conjugation of NPs with the B19 aptamer was confirmed by Fourier-transform infrared spectroscopy (FTIR) and 2,4,6-trinitrobenzene sulfonic acid (TNBSA) assay. Furthermore, the spherical morphology and core-shell structures of the Apt-NPs were evaluated by Field emission scanning electron microscopes (FE-SEM), atomic force microscopy (AFM), and high-resolution transmission electron microscopy (HR-TEM). In vitro cellular uptake of the BODIPY-labeled Apt-NPs was determined using confocal microscopy. The drugs were loaded with a double emulsification solvent evaporation method. Drug-loaded Apt-NPs significantly inhibited the tumor growth of U-87 stem cells by initiation of apoptosis and cell cycle arrest in G2/M and S via the down-regulation of autophagic and multi drug resistance (MDR) genes. Additionally, by their down-regulation by qPCR of CD133, CD44, SOX2, and Wnt/β-catenin, PI3K/AKT/mTOR (PAM) pathway, cell proliferation has substantially decreased. Addedly, simultaneous shortened telomere length with down-regulation of DKC1 and TERT subunits of telomerase by drug-loaded Apt-NPs increased apoptosis. Taken together, this dendrimer-based pharmaceutical drug delivery system along with B19 aptamer is capable of effectively transferring PTX and TMZ to U87 stem cells in consistent and without toxic effects.